Implementation of Enterprise Resource Planning (ERP) System Planning in Small and Medium Industries in Improving the Quality of Financial Reports: Implementasi Perencanaan Sistem Enterprise Resource Planning (ERP) pada Industri Kecil dan Menengah dalam Meningkatkan Kualitas Laporan Keuangan - Novitasari, Rika Dewi; Rahmawati, Imelda Dian (Universitas Muhammadiyah Sidoarjo, 2022)
ERP or Enterprise Resource Planning is an information application used for manufacturing or service companies that play a role in integrating business processes and dealing with operations, production and distribution departments in a company. The implementation of ERP software for IKM Foods Sejahtera was carried out because it saw problems in its business processes and saw the advantages possessed by this ERP system which can be adapted to the needs of IKM business processes. This research method uses qualitative, data collection is obtained from observation, in-depth interviews with SMEs, and taking documentation. The technique of determining the informants of this study was carried out by purposive sampling. The results of the study indicate that success in ERP implementation is very dependent on SMIs who must be able to manage changes in their business well and employees must also be able to apply new company procedures. The implementation of the Enterprise Resource Planning (ERP) system is running well in IKM Foods Prosperous Enterprises. But there is one case or problem that often occurs in the use of the system, namely the frequent occurrence of system errors. Based on the cases experienced by IKM Pangan Sejahtera Enterprises, such as the lack of structure in providing financial reports and other business activities, the implementation of ERP Midsuit is believed to make business processes easier in the future.